2009
DOI: 10.1111/j.1476-5381.2009.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of A‐940894: a potent histamine H4 receptor antagonist with anti‐inflammatory properties

Abstract: Background and purpose:The histamine H4 receptor is widely expressed in cells of immune origin and has been shown to play a role in a variety of inflammatory processes mediated by histamine. In this report, we describe the in vitro and in vivo anti-inflammatory properties of a potent histamine H4 receptor antagonist, A-940894 (4-piperazin-1-yl-6,7-dihydro-5H-benzo [6,7]Experimental approach: We have analysed the pharmacological profile of A-940894 at mouse native, rat recombinant and human recombinant and nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…70 In line with this, in several experimental models of intestinal damage, H 4 R antagonists were able to reduce neutrophil infiltration in intestinal mucosa. 19,21,24,[62][63][64] The gastric safety of H 4 R antagonists could be of major interest, when considering that the available anti-inflammatory drugs are still endowed with gastric toxicity; 14 nevertheless, the precise role of H 4 R in the gastric mucosa remains to be proven, since data with selective ligands are intriguing: the H 4 R agonist VUF8430…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…70 In line with this, in several experimental models of intestinal damage, H 4 R antagonists were able to reduce neutrophil infiltration in intestinal mucosa. 19,21,24,[62][63][64] The gastric safety of H 4 R antagonists could be of major interest, when considering that the available anti-inflammatory drugs are still endowed with gastric toxicity; 14 nevertheless, the precise role of H 4 R in the gastric mucosa remains to be proven, since data with selective ligands are intriguing: the H 4 R agonist VUF8430…”
Section: Acknowledgementsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] histAMinE h 4 R liGAnDs Since H 3 R and H 4 R are closely related, the early physiopharmacological characterization of the H 4 R was based on compounds retaining the ability to bind the H 3 R subtype. 25 The first selective H 4 R antagonist was the indolylpiperazine compound, JNJ7777120, which displayed high affinity (K i = 4 nM) for the human H 4 R with and a >1000-fold selectivity over the other histamine receptors, 26 thus becoming the "reference" H 4 R ligand in most experimental assays, also due to the lack of highly selective H 4 R agonists.…”
mentioning
confidence: 99%
“…25,26 Compounds with no supplier reference were synthesized in-house at the VU University Medicinal Chemistry department.…”
Section: Standard Mixturementioning
confidence: 99%
“…In an original publication from Lim et al (2009), a new improved selective H4 receptor agonist is reported, which will prove invaluable in the pharmacological dissection of this highly topical new drug target. A second original article from Strakhova et al (2009) reports the detailed pharmacological properties of a new potent highly selective H4 receptor antagonist, which adds to the range of pharmacophores available to study this histamine receptor. Improved pharmacokinetic properties displayed by this ligand should aid in its potential clinical use for chronic inflammatory disorders.…”
mentioning
confidence: 99%
“…In an original publication from Lim et al (2009), a new improved selective H4 receptor agonist is reported, which will prove invaluable in the pharmacological dissection of this highly topical new drug target. A second original article from Strakhova et al (2009) reports the detailed pharmacological properties of a new potent highly …”
mentioning
confidence: 99%